Cross‐sectional study on viraemia and shedding of porcine circovirus type 2 in a subclinically infected multiplier sow herd. (9th February 2019) - Eddicks, Matthias; Beuter, Bettina; Stuhldreier, Ralf; Nolte, Thomas; Reese, Sven; Sutter, Gerd; Ritzmann, Mathias; Fux, Robert
Abstract : Vertical and horizontal transmission of porcine circovirus type 2 (PCV2) plays an important role for the spread of PCV2 within piglet‐producing farms and following production steps. Further information is crucial to learn about the principles of PCV2 circulation among sows in piglet‐producing farms to improve preventive healthcare concerning porcine circovirus diseases (PCVD) in downstream production steps. The present study was conducted as a cross‐sectional study in a 400 sow multiplier herd in Germany with no PCV2 vaccination. Blood, faeces and saliva of the sows in all stages of production were tested for PCV2‐DNA by real‐time PCR. Results were analysed under respect of the parity and stage of production of the sows. PCV2‐DNA in faeces or saliva was observed especially in young sows. Highest rates of viraemia in productive sows were found in the early stages of pregnancy. The results revealed that particularly gilts from the quarantine and rearing area and sows up to the second parity play a major role for the spread of PCV2 and thus for the maintenance of PCV2 infection in sow herds. Furthermore, the stage of production had a significant influence on the detection rate of PCV2‐DNA in serum, saliva or faeces of the sows.